THE USAGE OF BRACING ON EARTHQUAKE RESISTANT BUILDINGS WITH PUSHOVER ANALYSIS: Pemakaian Bracing Pada Bangunan Tahan Gempa dengan Analisis Pushover - Anggraeni, Dwi Wahyu; Widayanto, Erno; Nurtanto, Dwi (Universitas Jember, 2017)
Most of Indonesia area is an earthquake- prone region. This is caused by the confluence of three major plates world that are subduction. Indo-Australian Plate colliding with the Eurasian plate off the coast of Sumatra, Java and Nusa Tenggara, while the Pacific plate in northern Guinea and North Maluku. In the vicinity of the meeting location this plate collision energy accumulated in the form of earthquake. The quake destroyed much of the multi-storey buildings that do not have adequate strength. Therefore , the higher the building, the greater the effects of the earthquake were received by the building. One way to acquire resistance to earthquake response was to add rigidity to a building. How to obtain the stiffness of a building is to install bracing for high-rise buildings. The purpose of this analysis was conducted to determine usage behavior particularly bracing displacement. The Results of this analysis showed a reduction in horizontal deviation of the building due to the addition of frame bracing. The difference in the percentage of horizontal deviation without bresing building and building using bresing X is 82.519%. While the difference in the percentage of horizontal deviation without order bresing building and building using bresing V is 64.904%. Sebagian besar wilayah Indonesia merupakan wilayah rawan gempa. Hal ini disebabkan oleh pertemuan tiga lempeng utama dunia yang bersifat subdaksi. Lempeng Indo- Australia bertabrakan dengan lempeng Eurasia di lepas pantai Sumatra, Jawa dan Nusa Tenggara, sedangkan lempeng Pasific di utara Irian dan Maluku Utara. Di sekitar lokasi pertemuan lempeng ini akumulasi energi tabrakan terkumpul sehingga lepas berupa gempa bumi. Gempa banyak menghancurkan bangunan- bangunan bertingkat yang tidak mempunyai kekuatan yang memadai. Oleh karena itu, semakin tinggi bangunan maka semakin besar pula efek gempa yang diterima oleh bangunan tersebut. Salah satu cara untuk memperoleh ketahanan terhadap respon gempa adalah menambah kekakuan pada suatu bangunan. Cara memperoleh kekakuan suatu bangunan adalah dengan memasang pengekang (bracing) untuk bangunan tinggi. Tujuan dari analisa ini dilakukan untuk mengetahui perilaku pemakaian bracing khususnya displacement. Hasil dari analisa ini menunjukkan terjadinya pengurangan simpangan horizontal gedung karena adanya penambahan rangka bracing. Selisih presentase simpangan horizontal gedung tanpa bresing dan gedung dengan menggunakan bresing X adalah 82,519%. Sedangkan selisih presentase simpangan horizontal gedung tanpa rangka bresing dan gedung dengan menggunakan bresing V adalah 64,904%.